Prospects for the use of chondroitin sulfate and glucosamine sulfate in the treatment of patients with obesity-associated osteoarthritis (metabolic syndrome) - I. Yu. Torshin; О. A. Gromova; A. M. Lila (IRBIS LLC, 2022)
The relationship between the pathophysiology of osteoarthritis (OA) and metabolic disorders (metabolic syndrome, obesity) is provided not only by mechanical causes (increased body weight pressure on the joints). A complex of molecular mechanisms, which mediates OA effect on the development of obesity, was established. Excessive activity of toll receptors, the NF-κB cascade, and metabolic disorders of endogenous chondroitin sulfates (CS) lead to chronic inflammation and the development of a complex of comorbid pathologies, including OA, atherosclerosis, and obesity. The relationship between insulin resistance and CS metabolism is also mediated by impaired genomic DNA methylation. Exogenous CS and glucosamine sulfate (GS) used in the long-term treatment of OA also contribute to the inhibition of the pathophysiology of obesity. By inhibiting O-glucosamination of intranuclear proteins (i.e., p53), GS can accelerate lipolysis of visceral fat. Anti-inflammatory effects of CS and GS is associated with inhibition of toll receptors and NF-κB, increased levels of antioxidant enzymes, regulation of expression of fibroblast growth factor 21, activation of adenosine monophosphate-activated protein kinase, and inhibition of secretion of chemoattractant protein MCP-1 and pancreatic lipase. Positive effect of CS and its oligosaccharides exposure on the pathophysiology of metabolic disorders is associated not only with a decrease in inflammation and normalization of fat metabolism but also with an improvement in the state of the intestinal microbiota. Experimental and clinical studies confirm the effects of CS and GS on body mass control. CS and GS are effective and safe when used in patients with OA associated with metabolic syndrome and/or obesity.